2018
DOI: 10.29333/ejmste/82625
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis on Cognitive Domain for the Malaysian Primary Four Textbook Series

Abstract: The purpose of this study is to investigate the levels of cognitive domains of Malaysian Mathematics primary four textbooks developed under the old and new curriculum based on Trends in International Mathematics and Science Study (TIMSS) 2015 Mathematics Framework. This study adopted content analysis where the mathematical tasks from the textbooks were classified in terms of type of tasks and cognitive domain. The results of the study showed that a large portion of mathematical tasks in the two textbooks are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
11
0
4
Order By: Relevance
“…In learning similar content, unity is employed through simultaneous and centralized examinations in terms of questions, dates and times, as in the Malaysian certificate of education (Sijil pelajaran Malaysia [SPM]) (examination special for form 5 or 17 years old pupils). This uniform examination is a unity agenda to enable pupils to be evaluated fairly and equally (Tan, Zaleha, & Mardhiyana, 2018). The least emphasized in the topic of fractions is information and communications technology embedded through suggested web site addresses in teachers' note.…”
Section: Resultsmentioning
confidence: 99%
“…In learning similar content, unity is employed through simultaneous and centralized examinations in terms of questions, dates and times, as in the Malaysian certificate of education (Sijil pelajaran Malaysia [SPM]) (examination special for form 5 or 17 years old pupils). This uniform examination is a unity agenda to enable pupils to be evaluated fairly and equally (Tan, Zaleha, & Mardhiyana, 2018). The least emphasized in the topic of fractions is information and communications technology embedded through suggested web site addresses in teachers' note.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have reported that both horizontal and vertical features of a textbook affect students' mathematical learning (Hadar, 2017;Stein et al, 2007). Therefore, we developed an analytical framework across the two dimensions based on several previous studies (Alajmi, 2012;Charalambous et al, 2010;Li et al, 2009;Son, 2012;Stein et al, 2007;Tan et al, 2018). Regarding the horizontal analysis, we examined the topic sequence and frequency (i.e., allocation of the topic).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…For example, the students who learned mathematics with a high level of cognitive demands problems are likely to develop high-order thinking skills, such as analyzing, reasoning, justifying, and evaluating. Conversely, the students who learned mathematics with a low level of cognitive demands tasks tended to develop low-order thinking skills, such as recalling and computation (Mullis et al, 2012;Tan et al, 2018). As different learning opportunities lead to different mathematical outcomes (Bellens et al, 2020;Hadar, 2017;van den Ham & Heinze, 2018), developing a high-quality mathematics textbook is a critical issue for educators.…”
mentioning
confidence: 99%
“…Penggunaan gambar rajah, jadual dan aplikasi situasi yang lebih mudah tertumpu dalam soalan penilaian di mana murid diuji untuk mengingat fakta dan maklumat yang telah dijelaskan dalam contoh-contoh soalan penerangan. Dalam buku teks KSSR 2011, domain soalan tahap literal merupakan domain yang terbanyak diuji berbanding soalan tahap inferensi dan penilaian (Kai Joo Tan, Zaleha Ismail & Mardhiyana Abidin, 2017). Hal ini membuktikan bahawa Kurikulum Semakan 2017 sememangnya telah menambah baik kurikulum sebelumnya agar lebih relevan dengan murid hari ini yang lebih terdedah dengan pelbagai maklumat.…”
Section: Aras Kognitif Bagi Soalan Dalam Buku Teks Matematik Kssr Tahunclassified
“…Walaubagaimanapun, jumlah keseluruhan soalan dalam buku teks Matematik KSSR Semakan 2017 iaitu sebanyak 921 soalan menunjukkan pengurangan dari bilangan jumlah soalan dalam buku teks Matematik KSSR 2011 yang mengandungi 1476 soalan (Kai JooTan, Zaleha Ismail & Mardhiyana Abidin, 2017). Hal ini disebabkan faktor perubahan pendekatan berbentuk modular dalam KSSR 2017 yang menyebabkan bilangan bab dikurangkan.…”
unclassified